The impact of Covid-19 pandemic on older adults with dementia and their caregivers: a narrative review - Stamati, Kyriaki; Argyri, Theodora; Balafouti, Angeliki; Ouissa, Antonia-Stefania; Eleni, Alevizopoulou (Magyar Gerontológia, 2022)
The purpose was to gather the existing literature, provide an up-to-date overview and, in the future, to continue the research for this important topic.